Rancang Bangun Aplikasi Remote Router Mikrotik Berbasis Android untuk Monitoring dan Manajemen Jaringan Secara Real-Time - Roby Novianto; Bambang Triraharjo; Muhammad Yanur; Anggia Nabilah (Sienna, 2026)
The rapid evolution of digital infrastructure in higher education institutions, particularly at Muhammadiyah University of Pringsewu, demands highly mobile and responsive network management. This study develops an Android-based remote router management application that integrates the MikroTik Application Programming Interface (API) to overcome the limitations of static desktop-based management. This study uses an empirical engineering approach with the Waterfall software development life cycle (SDLC) model, focusing on real-time monitoring of CPU, RAM, and bandwidth traffic, as well as active control of network interfaces and hotspot services. Field testing on the RB4011iGS+RM router shows that the implementation of asynchronous data processing and a Glassmorphism-based user interface significantly improves administrator situational awareness. The results show a 100% success rate in executing critical commands such as interface toggling and instant user disconnection (kick user), with an average response time of less than 1.1 seconds. The synthesis of findings confirms the hypothesis that this API-based mobile application improves network management efficiency and reduces response time during critical downtime. This study concludes that the transition to a mobile-first management ecosystem is a strategic necessity in maintaining high-availability digital services in modern academic environments.